Quality Measures in Upper Limb Surgery. (16th March 2016) - Kamal, Robin N.; Ring, David; Akelman, Edward; Yao, Jeffrey; Ruch, David S.; Richard, Marc; Ladd, Amy; Got, Christopher; Blazar, Philip; Kakar, Sanjeev
Abstract : Background: Quality measures are now commonplace and are increasingly tied to financial incentives. We reviewed the existing quality measures that address the upper limb and tested the null hypothesis that structure (capacity to deliver care), process (appropriate care), and outcome (the result of care) measures are equally represented. Methods: We systematically reviewed MEDLINE/PubMed, Embase, Google Scholar, the American Academy of Orthopaedic Surgeons Clinical Practice Guidelines, the National Quality Forum, the Agency for Healthcare Research and Quality, and the Physician Quality Reporting System for quality measures addressing upper limb surgery. Measures were characterized as structure, process, or outcome measures and were categorized according to their developer and their National Strategy for Quality Improvement in Health Care (National Quality Strategy) priority as articulated by the U.S. Department of Health & Human Services. Results: We identified 134 quality measures addressing the upper limb: 131 (98%) process and three (2%) outcome measures. The majority of the process measures address the National Quality Strategy priority of effective clinical care (90%), with the remainder addressing communication and care coordination (5%), person and caregiver-centered experience and outcomes (4%), and community/population health (1%). Conclusions: Our review identified opportunities to develop more measures in the structure and outcome domains as well as measures addressing patient and family engagement, public health, safety, care coordination, and efficient use of resources. The most common existing measures—process measures addressing care—might not be the best measures of upper limb surgery quality given the relative lack of evidence for their use in care improvement.